Successful treatment of groin pain syndrome in a pole-vault athlete with core stability exercise - Dello Lacono, A.; Maffulli, N.; Laver, L.; Padulo, J. (The Journal of Sports Medicine and Physical Fitness, 2017)
The purpose of this case report was to present a case of groin pain in a pole vault athlete describing the biomechanical features of the injury`s mechanism, acute medical management, and its successful rehabilitation. A 22-year-old professional pole-vaulter sustained an injury during a regular training session. The athlete reported significant left lower abdominal and left proximal adductor discomfort in all activities, including basic trunk motion when moving in bed, sit to stand, and walking, and was unable to return to the regular training. Clinical evaluation and imaging studies addressed the injury to a case of adductor-related groin pain associated with pubic symphysis degeneration. Treatment consisted of an exercise-based therapeutic protocol based on trunk and core muscle strengthening and stability program, with progressive motor and functional demands. Significant improvements in the overall clinical findings and functional outcomes were reported after 52 days of intervention when the athletes returned to his full athletic activity. These results suggest that an appropriate rehabilitation program, focused on trunk and core musculature stability exercise addressing to sport-related specific demands, should be considered as an optimal conservative method in the multidisciplinary approach for treatment of groin pain and prior to any surgical intervention.